Un modèle de prix de type intersectoriel pour le Québec - Truchon, Michel (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractThis paper presents a price model of the Input-Output variety. This model computes the changes in the production costs and the prices of goods resulting from changes in the prices of primary factors and imports and changes in indirect taxes. It assumes that all such changes are transmitted in whole and without delay to the users of goods. It is very close in spirit to the price model developed by Statistics Canada but it offers more general possibilities than the latter.